PAUL RICOEUR AND POPE JOHN PAUL II: A DIALOGUE ON THE PATH FROM FORGIVENESS TO PEACE (Isagoge - Journal of Humanities and Social Sciences, 2022)
Abstract: This article aims to analyze forgiveness according to Paul Recoeur view, using memory and forgetfulness as its starting point as well as the 1997 and 2002 messages of  Pope John Paul II, made for the celebration of the World Day of Peace, which deal with forgiveness and peace, in order to elaborate a dialogue about the path from forgiveness to peace.  Keywords: Forgiveness. Peace. Paul Ricoeur. Pope John Paul II.
Keywords: Forgiveness; Peace; Paul Ricoeur; Pope John Paul II